2014
DOI: 10.1159/000361017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cytogenetic Analysis in Stillbirth: Results from 481 Consecutive Cases

Abstract: Introduction: The underlying causes of stillbirth are heterogeneous and in many cases unexplained. Our aim was to conclude clinical results from karyotype and quantitative fluorescence-polymerase chain reaction (QF-PCR) analysis of all stillbirths occurring in Stockholm County between 2008 and 2012. By screening a subset of cases, we aimed to study the possible benefits of chromosomal microarray (CMA) in the analysis of the etiology of stillbirth. Methods: During 2008-2012, 481 stillbirths in Stockholm County … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…The pathologic processes implicated in fetal death include: infection 6584 , placental abruption, 5, 37, 70, 8592 vascular lesions of the placenta, 28, 35, 93100 preeclampsia, 41, 101105 fetal growth restriction 9, 106114 , maternal anti-fetal rejection, 35, 115120 metabolic disorders, 121133 genetic disorders, 80, 131, 134137 umbilical cord accident, 97, 138145 trauma 146148 , and placental senescence 22 ; however, most of the 47,000 stillbirths reported from developed countries in 2015 149 were classified as unknown etiology. It is currently believed that the causes of fetal loss change with gestational age: chromosomal abnormalities 150153 and infection 75 are the most common causes during the first half of pregnancy, placental causes (abruption or vascular abnormalities) 154156 , and maternal anti-fetal rejection 118 become the most common causes after 26 weeks until term 14 , after which the etiology of in most cases, especially after 40 weeks, is unknown 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic processes implicated in fetal death include: infection 6584 , placental abruption, 5, 37, 70, 8592 vascular lesions of the placenta, 28, 35, 93100 preeclampsia, 41, 101105 fetal growth restriction 9, 106114 , maternal anti-fetal rejection, 35, 115120 metabolic disorders, 121133 genetic disorders, 80, 131, 134137 umbilical cord accident, 97, 138145 trauma 146148 , and placental senescence 22 ; however, most of the 47,000 stillbirths reported from developed countries in 2015 149 were classified as unknown etiology. It is currently believed that the causes of fetal loss change with gestational age: chromosomal abnormalities 150153 and infection 75 are the most common causes during the first half of pregnancy, placental causes (abruption or vascular abnormalities) 154156 , and maternal anti-fetal rejection 118 become the most common causes after 26 weeks until term 14 , after which the etiology of in most cases, especially after 40 weeks, is unknown 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 10,44 provided information on the total number of cases with normal CMA in which karyotyping yielded a positive result: the karyotype was abnormal in eight of 670 cases in which CMA was negative, corresponding to a 1.2% (8/670) false-negative rate for CMA. The mean gestational age at stillbirth was 29 + 6 weeks, as provided by three of the studies 10,44,45 . Only two studies 10,45 reported on infectious disease (n = 23) and on fetal growth restriction (n = 35) as a possible cause for fetal demise.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Only two studies 10,45 reported on infectious disease (n = 23) and on fetal growth restriction (n = 35) as a possible cause for fetal demise. Data on fetal structural anomalies as a possible cause of stillbirth were provided in all seven studies; there were structural anomalies in 36% (323/903) of the cases with normal karyotype 10,25,27,[42][43][44][45] .…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations